2004
DOI: 10.1016/j.ejcts.2003.11.031
|View full text |Cite
|
Sign up to set email alerts
|

Basic fibroblast growth factor (bFGF) and vascular endothelial growth factor (VEGF) levels, as prognostic indicators in NSCLC

Abstract: Adenocarcinoma associated with lung cancer is regarded to have biological characteristics that distinguish it from squamous cell carcinoma. Node invasion may be associated with bFGF. bFGF and VEGF augment each other and are associated with leading to poor prognosis. The results of this study suggests that effective therapy to block angiogenesis may need to address at least both of these factors in cases of NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
45
2
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 16 publications
(13 reference statements)
4
45
2
1
Order By: Relevance
“…Nevertheless, our results are only correlative regarding the relationship between ADAM-12 and VEGF isoforms expression and further studies are needed to confirm our results and to precisely dissect the potential mechanisms linking ADAM proteases and tumour angiogenesis. The increased levels of VEGF-A found in tumours associated with N2 states when compared to those associated with N0 is in line with a recent report (Iwasaki et al, 2004) showing that VEGF expression in tumour samples is correlated with markedly poor prognosis.…”
Section: Discussionsupporting
confidence: 90%
“…Nevertheless, our results are only correlative regarding the relationship between ADAM-12 and VEGF isoforms expression and further studies are needed to confirm our results and to precisely dissect the potential mechanisms linking ADAM proteases and tumour angiogenesis. The increased levels of VEGF-A found in tumours associated with N2 states when compared to those associated with N0 is in line with a recent report (Iwasaki et al, 2004) showing that VEGF expression in tumour samples is correlated with markedly poor prognosis.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, the VEGF levels showed differences with respect to histological type. The levels of VEGF in adenocarcinoma were higher than for squamous cell carcinoma (Iwasaki et al, 2004). Therefore, VEGF may be important in the growth of lung adenocarcinoma.…”
Section: Discussionmentioning
confidence: 80%
“…Non-small cell lung cancer (NSCLC) tissue produces numerous growth factors, which are multifunctional and considered predictive of patient survival. The previous studies showed that a high expression of VEGF (≥25% of cells) was observed in squamous cell carcinomas and adenocarcinomas, and in all cases of large cell carcinomas (Iwasaki et al, 2004;Stefanou et al, 2003). The level of VEGF was independent prognostic factor in cases of NSCLC involving patients who had undergone curative resection (Iwasaki et al, 2004).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The homogenate was further homogenized with an ultrasonic homogenizer for 1 min on ice and then centrifuged at 10,000 g for 15 min at 4°C. 59 The supernatant was collected and stored at -70°C for subsequent analysis. TRAIL in serum and in tumor homogenate was determined using a commercial TRAIL ELISA kit.…”
Section: Cells (1 × 10mentioning
confidence: 99%